Some New Coupled Fixed-Point Findings Depending on Another Function in Fuzzy Cone Metric Spaces with Application. (8th July 2021) - Waheed, Muhammad Talha; Rehman, Saif Ur; Jan, Naeem; Gumaei, Abdu; Al-Rakhami, Mabrook
Abstract : In this paper, we introduce the new concept of coupled fixed-point (FP) results depending on another function in fuzzy cone metric spaces (FCM-spaces) and prove some unique coupled FP theorems under the modified contractive type conditions by using "the triangular property of fuzzy cone metric." Another function is self-mapping continuous, one-one, and subsequently convergent in FCM-spaces. In support of our results, we present illustrative examples. Moreover, as an application, we ensure the existence of a common solution of the two Volterra integral equations to uplift our work.